Potensi penerapan industri 4.0 dengan lean six sigma di industri pertahanan Indonesia: Sebuah Studi Komprehensif: Potensi penerapan industri 4.0 dengan lean six sigma di industri pertahanan Indonesia: Sebuah Studi Komprehensif - fatmawati fatmawati; Aries Sudiarso; Juprianto Juprianto; Rudy AG Gultom (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Amidst a rapidly evolving global landscape and ever-advancing technology, Indonesia's defense industry, as a vital strategic sector, must foster innovation to enhance its potential and competitiveness. An effective approach is the amalgamation of Industry 4.0 with Lean Six Sigma. Industry 4.0 encompasses technology-driven industrial advancements, including IoT, big data, AI, robotics, and integrated automation. In contrast, Lean Six Sigma focuses on elevating process quality and efficiency. This study explores the applicability of integrating Industry 4.0 with Lean Six Sigma in Indonesia's defense industry, aiming to expedite production, optimize resource utilization, and elevate operational efficiency. Lean Six Sigma aids in reducing error rates and production costs. The research employs a literature study method with comprehensive analysis of the implementation of Industry 4.0 technology and Lean Six Sigma methodology. The findings reveal that this integration holds immense potential for the defense industry. Nevertheless, it encounters challenges such as technology and infrastructure limitations, cybersecurity concerns, financial investments, human resource readiness, regulatory compliance, and system integration complexities. Recommended solutions comprise infrastructure and technology enhancements, bolstering cybersecurity measures, government financing and support, human resource development, research and development initiatives, and robust project management and system integration. In conclusion, adopting Industry 4.0 with Lean Six Sigma promises strategic advantages for Indonesia's defense industry. Collaborative efforts and government backing shall steer the defense industry towards an innovative and fiercely competitive future. Future researchers can broaden the scope, delve into obstacle analysis, and assess the impact to foster the defense industry's optimal growth